Injuries and functional performance status in young elite football players: a prospective 2-year monitoring - Sieland, J.; Krause, F.; Kalo, K.; Wilke, J.; Vogt, L.; Banzer, W.; Niederer, D. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Motor function, such as strength asymmetries of the lower extremities and impaired dynamic stability, have a predictive value for the risk of injury. The present study aimed to reveal potential associations between injury and motor performance. METHODS: Two hundred and five male youth elite (association) football (soccer) players (mean: 13.5±4.5 years, 57.2±30.2 kg, 168±35 cm) were included. A test battery was conducted twice per season, over two consecutive seasons (four times). Mobility (Sit and Reach Test, SnR), dynamic stability (Single Leg Hop for Distance, SLHD), linear sprinting speed (10 m, 30 m [s]), agility (Zig-Zag test with and without dribbling a ball [s]), jump performance (countermovement jump (CMJ) and drop jump (DJ), in cm) and maximal isometric voluntary force (MIVF, in N) of the knee extensors and flexors were assessed. All injuries occurring over the two-year period, as well as training and competition exposure time, were collected and used as grouping variables for statistical difference testing. RESULTS: One hundred and twenty-five injuries in 93 players occurred (an injury incidence of 2.7/1000 hours of exposure). Age was associated with injury incidence (r=0.191; P=0.006). Neither DJ, CMJ, SnR nor agility performance were statistically different between injured and non-injured participants (P>0.05). Group differences did occur for sprint and strength (P=0.011; P=0.016), but these lapsed after the inclusion of age as a covariate. Only for SLHD symmetry was a non-significant trend evident after the correction for age (P=0.08). CONCLUSIONS: The occurrence of musculoskeletal injuries in junior football players are, probably, not related to baseline motor function. Group differences between injured and non-injured youth elite football players are mostly explained by age. Only the symmetry in SLHD could be a potential risk factor for injuries and merits further investigation.